Internship Reports and Monograph Entitled "Drug Repurposing for Skin Cancer Treatment: A Nanotechnological Approach" - Martins, Maria de Melo Cartaxo Correia (2023)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia